IMPLEMENTASI SMART CONTRACT PADA PEMILU ELEKTRONIK BERBASIS BLOCKCHAIN UNTUK MENJAMIN VALIDITAS DAN KEAMANAN DATA - Novemli Firdaus; Wakhinuddin; Asrul Huda; Mukhlidi Muskhin (EDU RESEARCH, 2024)
Elections are an important foundation in a democratic system, but are often marred by various problems such as vote manipulation and lack of transparency. This research analyzes the use of blockchain technology and smart contracts in electronic election systems to increase security, transparency and vote validity. The method used is Research and Development (R&D) which includes problem identification, literature study, system design, prototype development, as well as testing and evaluation. The research results show that blockchain implementation can automate the voting process, ensure data authenticity and reduce the potential for fraud. In addition, this research adds a facial verification feature as an additional layer of security that was not available in previous research, thereby increasing the integrity of the election system. By utilizing this technology, blockchain-based electronic elections are expected to provide innovative solutions that increase public confidence in election results, as well as create a more modern and efficient democratic system.